Portaria PR/BA nº 347, de 22 de agosto de 2018 - Fabio Conrado Loula (DMPF-e - Administrativo, n. 161, 24/8/2018, p. 13-14., 2018)
Altera o caput do art. 2º da Portaria PR/BA Nº 233, de 21 de maio de 2018.